2003
DOI: 10.1080/00288233.2003.9513560
|View full text |Cite
|
Sign up to set email alerts
|

Influences of grazing and exclosure on carbon sequestration in degraded sandy grassland, Inner Mongolia, north China

Abstract: Livestock grazing is recognised as one of the main causes of vegetation and soil degradation/desertification in the semi-arid Horqin sandy steppe of northern China. In this paper, soilplant system carbon (C) in a representative degraded sandy grassland in the Horqin sandy steppe (42°58' N, 120°42'E altitude c. 360 m a.s.l.) was measured. Three situations: long-term continuous grazing (CG), exclosure for 5 years (5EX), and exclosure for 10 years (10EX), were compared to assess the effect of grazing management o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…Some field studies have proposed exclosure as an effective approach for restoring vegetation and improving C storage of the grassland Su et al, 2003), while others demonstrated that exclosure has had negative effects on C sequestration in grasslands (Reeder and Schuman, 2002). This apparent contradiction can be explained by the different evolutionary processes, degrees of degradation and grazing history in these grassland communities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some field studies have proposed exclosure as an effective approach for restoring vegetation and improving C storage of the grassland Su et al, 2003), while others demonstrated that exclosure has had negative effects on C sequestration in grasslands (Reeder and Schuman, 2002). This apparent contradiction can be explained by the different evolutionary processes, degrees of degradation and grazing history in these grassland communities.…”
Section: Discussionmentioning
confidence: 99%
“…Livestock exclosures have a potential value in assessing the effects of grazing upon vegetation and C sequestration in the grasslands (Bock et al, 1984;Cheng et al, 2011;He et al, 2011;Li et al, 2012;Su et al, 2003). Exclosures appear to favor higher community diversity and productivity compared with grazing in the arid grasslands (Bock et al, 1984;Cheng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the two grasslands, continuous grazing resulted in a significant increase in soil BD (Su et al 2003) in upper soil layers (0-40 cm); this may result from livestock tramping. For the cropland, long-term intensive farming led to a decrease of Bd in surface soil layers, except for the plough pan.…”
Section: Bulk Density and Soc Contentsmentioning
confidence: 99%